A critical overview of current myofascial pain literature – March 2015. Issue 2 (April 2015) - Dommerholt, Jan; Layton, Michelle; Hooks, Todd; Grieve, Rob
Summary: The second article in this review series considers multiple recent publications about myofascial pain, trigger points (TrPs) and other related topics. The article is divided into several sections, including a Basic Research section (4 articles), a section on Soft Tissue Approaches (5 articles), a Dry Needling and Acupuncture section (7 articles), an Injection section (2 articles), a section on. Modalities (1 article), Other Clinical Approaches (3 articles) and finally a Reviews section (7 articles). The thirty publications reviewed in this article originated in all corners of the world.